Wireless multilateral devices for optogenetic studies of individual and social behaviors - Yang, Yiyuan; Wu, Mingzheng; Vázquez-Guardado, Abraham; Wegener, Amy J.; Grajales-Reyes, Jose G.; Deng, Yujun; Wang, Taoyi; Avila, Raudel; Moreno, Justin A.; Minkowicz, Samuel; Dumrongprechachan, Vasin; Lee, Jungyup; et al. (Nature neuroscience, 2021)
Advanced technologies for controlled delivery of light to targeted locations in biological tissues are essential to neuroscience research that applies optogenetics in animal models. Fully implantable, miniaturized devices with wireless control and power-harvesting strategies offer an appealing set of attributes in this context, particularly for studies that are incompatible with conventional fiber-optic approaches or battery-powered head stages. Limited programmable control and narrow options in illumination profiles constrain the use of existing devices. The results reported here overcome these drawbacks via two platforms, both with real-time user programmability over multiple independent light sources, in head-mounted and back-mounted designs. Engineering studies of the optoelectronic and thermal properties of these systems define their capabilities and key design considerations. Neuroscience applications demonstrate that induction of interbrain neuronal synchrony in the medial prefrontal cortex shapes social interaction within groups of mice, highlighting the power of real-time subject-specific programmability of the wireless optogenetic platforms introduced here. The authors introduce advanced technology for controlled wireless light delivery in optogenetics applications with real-time user programming capacity. The utility of the platform is highlighted by induction of neural synchrony to modify social behavior in mice.